Mechanism of crack branching in the fatigue crack growth path of 2324-T39 Aluminium alloy - Lu Songsong; Bao Rui; Zhang Ting; Fei Binjun (Fracture and Structural Integrity)
The crack growth behavior in 2324-T39 aluminium alloy was experimentally investigated. Two types of crack branching were observed. The mechanism of an uncommon crack branching which results from the link up of secondary crack with the main crack was focused on. The crack paths were observed with optical microscope and in-situ SEM. Finite element crack tip simulation was performed to investigate the relationship between plastic zone size and the location of the secondary crack. Tests and analysis results indicate that the secondary crack initiates near the plastic zone boundary and from the subsurface. The mechanism of this kind crack branching relates to the interaction of grain size and plastic zone size.